Infectious bronchitis virus: detection and vaccine Strain differentiation by semi-nested RT-PCR - Okino, CH [UNESP]; Montassier, MFSM [UNESP]; Givisiez, PEN [UNESP]; Furuyama, CRAG; Brentano, L; Montassier, Helio Jose [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
A semi-nested reverse transcription-polymerase chain reaction (Semi-N-RT-PCR) was developed and used to detect the S glycoprotein gene of infectious bronchitis virus (IBV) strains and to discriminate H120 vaccine strain from other strains. Viral RNA was extracted from the allantoic fluid of chicken embryos and from tissues of chickens experimentally infected with different strains of IBV. Amplification and identification of the viral RNA was performed using two sets of primers complementary to a region of the S glycoprotein gene in the Semi-N-RT-PCR assay. The pair of primers used in the first PCR consisted of universal oligonucleotides flanking a more variable region of S1-S2 gene. The second primer pair was used in the Semi-N-RT-PCR and was comprised of one of the primers from the first universal pair together with either another universal internal oligolucleotide or a oligonucleotide sequence specific for the H120 strain of IBV. The universal primers detected all reference IBV strains and field isolates tested herein. The Semi-N-RT-PCR had high sensitivity and specificity, and was able to differentiate the H120 vaccine strain from other reference IBV strains; including M41 strain. All tissue samples collected from chickens experimentally infected with H120 or M41 strains were positive in the semi-nested RT-PCR using universal primers, while only the H120-infected tissue samples were amplified by the set of primers containing the H120-oligonucleotide. In conclusion, the ability of Semi-N-RT-PCR to detect distinct IBV strains and preliminarily discriminate the vaccine strain (H120) closes a diagnostic gap and offers the opportunity to use comprehensive PCR procedures for the IBV diagnosis.
Keywords: detection; Differentiation; Infectious bronchitis virus; semi-nested RT-PCR; vaccine strain